The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1515/chem-2020-0089
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a novel ginkgolide B niosomal composite drug

Abstract: Ginkgolide B (GB) and Puerarin (Pue) are active pharmaceutical ingredients for the treatment of Parkinson’s disease (PD); however, both are poorly water-soluble, which limits their bioavailability. The present study used the niosome vesicle encapsulation technique to prepare a novel GB composite drug. The conditions for GB–Pue niosomal complex preparation were as follows: a hydration temperature of 60°C, a hydrophilic–lipophilic balance of 10.5, a drug–carrier mass ratio of 8:100, and a surfactant–cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Ginkgolide B, a diterpene extracted from Ginkgo biloba, has been proven to have potential for the treatment of Alzheimer's disease, since by having an inhibiting role on the platelet-activating factor, it has been shown to protect neuronal cells that were damaged by Aβ accumulation from further harm. Additionally, this compound has also been shown to reduce the apoptosis induced by the Aβ peptide via the brain-derived neurotrophic factor mechanism, and to have reparative and protective effects on Aβ peptide-damaged mitochondria [115,[170][171][172]. Moreover, ginkgolide B also appears to be promising in Parkinson's disease-related pathophysiology factors, since it was proved to regulate the D-glutamic acid pathway, hence affecting glutamic acid and dopamine metabolism, which are connected to the early stages of this disease [115,173,174].…”
Section: Niosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginkgolide B, a diterpene extracted from Ginkgo biloba, has been proven to have potential for the treatment of Alzheimer's disease, since by having an inhibiting role on the platelet-activating factor, it has been shown to protect neuronal cells that were damaged by Aβ accumulation from further harm. Additionally, this compound has also been shown to reduce the apoptosis induced by the Aβ peptide via the brain-derived neurotrophic factor mechanism, and to have reparative and protective effects on Aβ peptide-damaged mitochondria [115,[170][171][172]. Moreover, ginkgolide B also appears to be promising in Parkinson's disease-related pathophysiology factors, since it was proved to regulate the D-glutamic acid pathway, hence affecting glutamic acid and dopamine metabolism, which are connected to the early stages of this disease [115,173,174].…”
Section: Niosomesmentioning
confidence: 99%
“…Additionally, this compound has also been shown to reduce the apoptosis induced by the Aβ peptide via the brain-derived neurotrophic factor mechanism, and to have reparative and protective effects on Aβ peptide-damaged mitochondria [115,[170][171][172]. Moreover, ginkgolide B also appears to be promising in Parkinson's disease-related pathophysiology factors, since it was proved to regulate the D-glutamic acid pathway, hence affecting glutamic acid and dopamine metabolism, which are connected to the early stages of this disease [115,173,174]. On the other hand, puerarin, an isoflavone extracted from Pueraria genus plants, has also proven to have potentially beneficial effects in both Alzheimer's and Parkinson's disease, due to its antioxidant properties (free radical scavenging, and endogenous antioxidant activity increase), regulation of calcium signaling pathways, functional stabilization of amino acid neurotransmitters and maintenance of the dynamic balance between them (excitatory vs. inhibitory), and regulation of neuronal apoptosis and overall cell damage.…”
Section: Niosomesmentioning
confidence: 99%
“…Functional “inner and outer” drug fiber membranes can also be used to regenerate tissue [ 179 ]. Additionally, the dioleyl phosphatidic acid (DOPA) carrier wrapped puerarin 5-FU formed biodegradable polymer nanoparticles, and novel puerarin nanoemulsion (nanoPue), pegylated nanoparticles, GO-based nanoplatform, and vesicular encapsulation technology-based GB-PUE-ribosome complex intravenous injection preparations can also improve the efficacy of puerarin [ 180 , 181 , 182 , 183 , 184 ].…”
Section: A New Drug Delivery System For Puerarinmentioning
confidence: 99%
“…Borneol, a bicyclic monoterpene that exerts anti-inflammatory and antiepileptic activities, possesses BBB permeability-enhancing effect by inhibiting P-gp and MRPs in the BBB and disassembling TJ proteins, reversibly [ 106 ]. Recent studies reported that borneol-modified nanoparticles and niosomes could enhance the brain uptake of loaded drugs, dopamine, and ginkgolide B and puerarin, respectively, compared to the plane nanoparticle and plane niosomes, thereby exerting more potent therapeutic effects in Parkinson’s disease-induced model [ 107 , 108 ].…”
Section: Natural Compound–drug Interactions In Brain Disordersmentioning
confidence: 99%